Assessment and Management for Speech in Facial Palsy: A Review Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Facial nerve palsy is the common problem of facial muscles weakness and facial appearance, mainly resultingof temporary or permanent damage of any structures innervated by the facial nerve. It can be congenital oracquired. About 45 to 75 % of unilateral facial nerve palsy cases are still idiopathic. Facial palsy impairmentsignificantly affects swallowing, articulation, and lip sufficiency. Diminished facial expression can posechallenges in face-to-face communications that affects their psychological consequences which lead tonegative impact on the quality of life. This article reviews on the assessment and management for thecommunication and quality of life. Speech-language therapy in facial paralysis aims in the rehabilitation oforal functions such as verbal and non-verbal communication, swallowing and vegetative skills.
Keywords: Facial palsy, idiopathic, musculature, articulation, rehabilitation.